2004
DOI: 10.1103/physrevd.69.094507
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of charmonium systems after deconfinement

Abstract: We present a study of charmonia in hot gluonic plasma, for temperatures up to three times the deconfinement transition temperature T c . qq systems with quark masses close to the charm mass and different spin-parity quantum numbers were studied on very fine isotropic lattices. The analysis of temporal correlators, and spectral functions constructed from them, shows that the J/ and c survive up to quite high temperatures, with little observable change up to 1.5T c , and then gradually weaken and disappear by 3T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

68
645
8
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(728 citation statements)
references
References 41 publications
68
645
8
2
Order By: Relevance
“…Lattice calculation of charmonium spectral functions appeared recently and suggested, contrary to potential models, that J/ψ and η c survive at temperatures as high as 1.6T c [9,10,11,12]. It has been also found that χ c melts at temperature of about 1.1T c [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lattice calculation of charmonium spectral functions appeared recently and suggested, contrary to potential models, that J/ψ and η c survive at temperatures as high as 1.6T c [9,10,11,12]. It has been also found that χ c melts at temperature of about 1.1T c [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…temperature dependence due to the integration kernel, following Ref. [12] for each temperature we calculate the so-called reconstructed correlator…”
Section: Charmonia Correlators and Spectral Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of quarkonia correlators and potentials in finite-T lattice QCD indicate that the different charmonium and bottomonium states dissociate at temperatures for which the colour (Debye) screening radius of the medium falls below their corresponding Q Q binding radii. Recent lattice analyses of the quarkonia spectral functions [119][120][121][122] indicate that the ground states (J/ψ and ϒ) survive at least up to T ≈ 2 T c whereas the less bound χ c and ψ melt near T c . Experimental confirmation of such a threshold-like dissociation pattern would provide a direct means to determine the transition temperature reached in the system and their comparison to ab initio lattice QCD predictions.…”
Section: Quarkonia: Critical Temperature and Energy Densitymentioning
confidence: 99%
“…Among these theoretical developments are the phenomenologically successful statistical model for J/ψ production [3,4,5], based on a coalescence assumption near T c [5], and the recent lattice calculations, showing strong evidence that the J/ψ will survive up to 1.6T c [6,7,8,9]. While these two results seem at odd with each other, it only suggests that one still needs a more detailed understanding of the properties of heavy quark system in the quark gluon plasma, especially for temperatures between T c and 1.6T c , before a consistent picture of J/ψ suppression in heavy ion collision is achieved.…”
Section: Introductionmentioning
confidence: 99%